FAKTOR - FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA BERWIRAUSAHA PADA MASA PANDEMI COVID 19 ( Studi Kasus : Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Katolik Santo Thomas Medan ) - Tamba, Darwis; Sagala, Roslinda; Ritonga, Sinar (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study is to analyze what factors dominantly influence student interest in entrepreneurship during the COVID-19 pandemic. Benefits of the study, to determine the dominant factors influencing student interest in entrepreneurship during the COVID-19 pandemic. The population is all students majoring in management who have taken entrepreneurship courses while the sample size is 125 students, data collection methods are through questionnaires, documentation and interviews, data analysis methods with factor analysis. The results showed that the characteristics of the respondents based on the education level of the dominant parents were high school, the occupation of the parents was dominant farmers and the income of the parents was more dominant 3.1 million - 4 million. Based on 25 (twenty five) factors, it turns out that all factors can be grouped into 8 (eight) which are the dominant factors, namely: The first factor consists of: Parents' work, Able to find opportunities, Has access to capital, Encouragement from parents, Ability to see opportunities and Entrepreneurial field practice, Second Factor consists of: Able to do business alone, Able to plan activities, Able to create opportunities, Maintain prestige, Have an entrepreneurial mentality and be able to determine business direction, Third Factor consists of: Parents' mindset, Parents' education and your encouragement, the fourth factor consists of: very high profits, the fifth factor consists of: leadership skills, able to see the future and self-confidence, the sixth factor consists of: independent effort and unyielding attitude, the seventh factor consists of: business confidence developing and self-confidence and Factor Eight consists of: Income prospect n High and Income cannot be measured. Based on the results of the study, it is better to increase environmental factors regarding sibling encouragement, because siblings are the closest environment to influence, so it is effective to increase interest in entrepreneurship and parents' mindsets, emotionally affect someone so that, if the parents have an entrepreneurial spirit embedded in them. it will affect their children. Entrepreneurship courses that have been applied in the curriculum should be applied to the concepts of more applicable theories. With the application of entrepreneurship that students learn, they will be encouraged to become job creators, not job seekers.